2016
DOI: 10.1002/jcb.25496
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β Signaling in Cancer

Abstract: The transforming growth factor-β (TGF-β) is a family of structurally related proteins that comprises of TGF-β, activins/inhibins, and bone morphogenic proteins (BMPs). Members of the TGF-β family control numerous cellular functions including proliferation, apoptosis, differentiation, epithelial-mesenchymal transition (EMT), and migration. The first identified member, TGF-β is implicated in several human diseases, such as vascular diseases, autoimmune disorders, and carcinogenesis. Activation of the TGF-β recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
308
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(318 citation statements)
references
References 49 publications
7
308
0
3
Order By: Relevance
“…TGF-β1 has multiple functions in tumors [1922]. On the one hand, it induces EMT in tumor cells, while on the other hand, it can suppress the invasion and metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 has multiple functions in tumors [1922]. On the one hand, it induces EMT in tumor cells, while on the other hand, it can suppress the invasion and metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The later identification of EMT-induction and other effects of TGF-β strengthened this notion of the dual effects of TGF-β on tumor development and progression, and also prompted the emerge of a modified notion of the dual effects of TGF-β, which emphasized the tumor suppressing effect at early stage and the promoting effect at late stage of tumorigenesis. According to this understanding, TGF-β was considered to be a tumor suppressor at early stage of tumorigenesis due to its growth arrest and/or pro-apoptotic effect on cells, and a tumor promoter at late stage of tumorigenesis because of its other effects including the induction of EMT [26][27][28][29][30]. However, several basic aspects of this proposed notion need to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Unequivocally, transforming growth factor-β (TGF-β) is a major inducer of different subtypes of EMT, including development, fibrosis, and carcinogenesis, in various cells [28]. In particular, TGF-β plays a major role in carcinoma progression into a motile, invasive state in which cells migrate and form a metastasis during tumour development, whereas in the early stages of tumour growth, TGF-β may have a tumour suppressive effect by inducing growth arrest and apoptosis [18,28,29]. Hence, as natural intracellular receptors of TGF-β, many Smad proteins, such as Smad2, Smad3 and Smad4, are phosphorylated after TGF-β binding to regulate the transcription of related genes and may participate in EMT as well [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, TGF-β plays a major role in carcinoma progression into a motile, invasive state in which cells migrate and form a metastasis during tumour development, whereas in the early stages of tumour growth, TGF-β may have a tumour suppressive effect by inducing growth arrest and apoptosis [18,28,29]. Hence, as natural intracellular receptors of TGF-β, many Smad proteins, such as Smad2, Smad3 and Smad4, are phosphorylated after TGF-β binding to regulate the transcription of related genes and may participate in EMT as well [28,29]. In addition, previous reports have indicated that the transcription factor signal transducer and activator of transcription 3 (STAT3) can induce EMT in cancer cells through activation of TWIST gene expression by cooperating with the EGFR [30].…”
Section: Introductionmentioning
confidence: 99%